Investigating the causal relationship between gut microbiota and gastroenteropancreatic neuroendocrine neoplasms: a bidirectional Mendelian randomization study - Zhang, Chun-yu; Jiang, Shi-jing; Cao, Jing-jing; Xu, Yan; Wang, Xiao-yu; Li, Rui; Miao, Zhi-wei (Frontiers in Microbiology, 2024)
The interaction between the intestinal flora and gastroenteropancreatic neuroendocrine neoplasms (GEP-NENs) remains poorly understood, despite the known effect of the gut microbiota on gastrointestinal adenocarcinomas. Hence, the present research aimed to determine the potential causal correlation between the intestinal flora and GEP-NENs by conducting a bidirectional Mendelian randomization (MR) analysis.Methods: Two-sample MR analysis was conducted using the summary statistics of the gut microbiota from the MiBioGen consortium and those of GEP-NENs from the FinnGen research project. The inverse-variance weighted approach was utilized as the primary analytical method. To enhance the robustness of our findings, multiple sensitivity tests were performed, including Cochran's Q test for evaluating heterogeneity, the MR-Egger intercept test to detect horizontal pleiotropy, and the MR-PRESSO test to identify outliers and assess pleiotropy bias. Additionally, a leave-one-out analysis was performed to validate the consistency of our findings. The MR-Steiger test was also utilized to determine the causal direction in the correlation between the gut microbiota and GEP-NENs. Finally, a reverse MR analysis was performed to assess reverse causality between the intestinal flora and GEP-NENs.We identified 42 taxa of the gut microbiota that were potentially causally associated with GEP-NENs; of these taxa, 7, 8, 11, and 16 taxa were causally associated with pancreatic NENs, colorectal NENs, small intestinal NENs, and gastric NENs, respectively. After adjusting for false discovery rate (FDR) correction, we found significant causal links of Euryarchaeota with small intestinal NENs and Family XIII UCG-001 with gastric NENs. The sensitivity analyses confirmed the stability of these correlations. In the reverse MR analysis, colorectal NENs and small intestinal NENs were 2 found to be associated with variations in 8 and 6 different taxa of the gut microbiota, respectively. After adjusting for FDR correction, no significant causal links were detected between GEP-NENs and the intestinal flora.The present study reveals a potential causal association between certain taxa of the intestinal flora and GEP-NENs, thus providing new perspectives regarding the role of the intestinal flora in the development of these tumors. These insights could provide innovative approaches to screen and prevent these diseases.